Genetic diversity and population structure of a Peruvian cattle herd using SNP data - Corredor, Flor-Anita; Figueroa, Deyanira; Estrada, Richard; Salazar, Wilian; Quilcate, Carlos; Vásquez, Héctor V.; Gonzales, Jhony; Maicelo, Jorge L.; Medina, Percy; Arbizu, Carlos I. (Frontiers in Genetics, 2023)
New-generation sequencing technologies, among them SNP chips for massive genotyping, are useful for the effective management of genetic resources. To date, molecular studies in Peruvian cattle are still scarce. For the first time, the genetic diversity and population structure of a reproductive nucleus cattle herd of four commercial breeds from a Peruvian institution were determined. This nucleus comprises Brahman (N=9), Braunvieh (N=9), Gyr (N=5), and Simmental (N=15) breeds. Additionally, samples from a locally adapted creole cattle, the Arequipa Fighting Bull (AFB, N=9), were incorporated. Female individuals were genotyped with the GGPBovine100K and males with the BovineHD. Quality control, and the proportion of polymorphic SNPs, minor allele frequency, expected heterozygosity, observed heterozygosity, and inbreeding coefficient were estimated for the five breeds. Admixture, principal component analysis (PCA), and discriminant analysis of principal components (DAPC) were performed. Also, a dendrogram was constructed using the Neighbor-Joining (NJ) clustering algorithm. The genetic diversity indices in all breeds showed a high proportion of polymorphic SNPs, varying from 51.42% in Gyr to 97.58% in AFB. Also, AFB showed the highest expected heterozygosity estimate (0.41±0.01), while Brahman the lowest (0.33±0.01). Besides, Braunvieh possessed the highest observed heterozygosity (0.43±0.01), while Brahman the lowest (0.37±0.02), indicating that Brahman was less diverse. According to the molecular variance analysis, 75.71% of the variance occurs within individuals, whereas 24.29% occurs among populations. The pairwise genetic differentiation estimates (FST) between breeds showed values that ranged from 0.08 (Braunvieh vs AFB) to 0.37 (Brahman vs Braunvieh). Similarly, pairwise Reynold’s distance ranged from 0.09 (Braunvieh vs AFB) to 0.46 (Brahman vs Braunvieh) . The dendrogram, similar to the PCA, identified two groups, showing a clear separation between Bos indicus (Brahman and Gyr) and B. taurus breeds (Braunvieh, Simmental and AFB). Simmental and Braunvieh grouped closely with the AFB cattle. Similar results were obtained for the population structure analysis with K =2. The results from this study would contribute to the appropriate management, avoiding loss of genetic variability in these breeds and for future improvements in this nucleus. Additional work is needed to speed up the breeding process in the Peruvian cattle system.